2020
DOI: 10.1016/j.brainresbull.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of very small embryonic-like stem cells in the neuroinflammation induced by social isolation stress: Introduction of a new paradigm

Abstract: Background: Lack of social contacts could induce psychiatric features and lead to various behavioral and neurochemical abnormalities in rodents. Social isolation stress (SIS) is a valid paradigm of depressive-and anxiety-like behaviors in animals. It has demonstrated that psychiatric disorder could affect the peripheral blood population of very small embryonic-like stem cells (VSELs). The aim of the current study is to evaluate the role of VSELs in behavioral impairments induced by SIS through neuroinflammatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Microglia in less ramified form is considered activated or intermediate active, which explains the reduction in the hull span size [ 51 , 55 ]. These results are consistent with the findings from several groups that demonstrated the activated microglia contribute to anxiety induced by social isolation [ 56 , 57 ]. In addition, several studies showed that microgliosis mediate synapses loss that is considered the earliest manifestation of AD pathology [ 58 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Microglia in less ramified form is considered activated or intermediate active, which explains the reduction in the hull span size [ 51 , 55 ]. These results are consistent with the findings from several groups that demonstrated the activated microglia contribute to anxiety induced by social isolation [ 56 , 57 ]. In addition, several studies showed that microgliosis mediate synapses loss that is considered the earliest manifestation of AD pathology [ 58 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…temperature: 22 ± 2°C, humidity: 50 ± 10%, 12‐h light‐dark cycle, and ad‐libitum access to food and water for a period of 5 weeks. Socially conditioned mice were placed in Plexiglas boxes (25 cm × 25 cm × 15 cm) (6 mice per cage) and IC animals were placed individually in Plexiglas boxes (24 cm × 17 cm × 12 cm) (Haj‐Mirzaian et al., 2017, Haj‐Mirzaian et al., 2020). In order to diminish handling and social interaction cages of IC animals were cleaned weekly by the same experimenter.…”
Section: Methodsmentioning
confidence: 99%
“…We also measured serum levels of interleukin-1 (IL-1), interleukin-6 (IL-6), TNFα, and the gene expression of CYP450 in order to detect the extent of inflammation and the hepatic enzymatic capacity, respectively. -Mirzaian et al, 2017, Haj-Mirzaian et al, 2020. In order to diminish handling and social interaction cages of IC animals were cleaned weekly by the same experimenter.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study, after sacri cing mice, we resected femur and tibia from surrounding tissue of both normal and socially isolated animals, and then ush the bones with warm medium (5% fetal bovine serum (FBS), + 1% Streptomycin) through a 70 µm nylon [32]. Then centrifuged the samples 250 x g for 10 min in 4° C; and discarded the supernatant and resuspend the cells with approximately 25 ml of medium [33]. We checked and counted the cells in a counting chamber with a light microscope and calculated the number of observed cells.…”
Section: Isolation and Culture Of Monocytes For In-vitro Studymentioning
confidence: 99%